The safety profile of drug treatment of alzheimer's disease - V. А. Moroz (Zaporožskij Medicinskij Žurnal)
Despite the fact that Alzheimer's disease is being intensively studied for many years, its main etiopathogenic mechanisms are still unknown. At the same time, given the prognosis of the disease and its prevalence, the problem of adequate medical treatment is an important medical and social problem. The problem is compounded by the fact that in recent years there has been a tendency of expanding the concept of the disease.